The Public Baptism of Muslims in Early Modern Spain and Portugal: Forging Communal Identity through Collective Emotional Display. (19th May 2015) - Soyer, Francois
Abstract : This article seeks to consider the role played by emotions, or rather emotional display, in the public spectacle of the conversion of infidels in early modern Spain and Portugal. It begins with a concise examination of the ritual of public baptism, based chiefly on evidence gleaned from surviving accounts of four large ceremonies held in Lisbon (1588), Seville (1625 and 1672), and Barcelona (1723), as well as two smaller public baptisms in the village of Fitero in Spain (1659) and the town of Estremoz in Portugal (1739). It then focuses on the account of the public baptism of a Muslim that took place in Seville in 1625 — by far the most detailed account — to highlight the importance given to the emotional responses of both the convert (to establish his sincerity) and the spectators in these ceremonies. Finally, it examines the wider social function of these spectacles and argues that their organisers, beyond their own personal or institutional motives, exploited the conversion of infidels in order to create a sense of communal identity binding the spectators together through their collective emotional response to specific symbols.